REGULASI DIRI TERHADAP BELAJAR MAHASISWA TINGKAT AKHIR YANG SUDAH MENIKAH DI UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Citra Ramadhanty; Ahmad Fauzi (At-Taujih : Bimbingan dan Konseling Islam, 2024)
This study was conducted to find out and understand more deeply about self-regulation of married final year students. Self-regulation in learning has a big role in achieving one's achievement. In the independent learning process, one needs to set their learning goals, make their lesson plans, choose their learning strategies, monitor their learning processes, evaluate and suppress their learning disorders. The approach used is a descriptive qualitative approach. Research subjects were selected by purposive sampling technique. And the data collection techniques used were observation and interviews. Interviews were conducted using the WhatsApp application. The results of this study found that the three resource persons used self-regulation in learning in the form of cognitive regulation, emotional regulation and motivation regulation. Self-regulation in learning carried out by the speakers is influenced by the environment, self-motivation and self-confidence. Self-regulation creates feelings of security, calm, comfort and creates a sense of confidence and motivation for themselves to immediately complete their final project or thesis.